Role of a community clinic for Prevention of Female Genital Fistula - Karmakar, Anirudha; Huda, Sk Nazmul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe how a community clinic in Bangladesh playing role in prevention of female genital fistula in remote villages in Bangladesh. Methods: Fistula service related program data and records of a community clinic during January 2018 to September 2018 have been used to prepare this report. Results: Mobilizing the Community Clinic Group and Community Clinic Support Groups, a community clinic centered plan of action for prevention and care of fistula was prepared. Universal coverage of obstructed labor was achieved during this period through mobilizing the community clinic support groups. There was no case of early marriage in the coverage area during this time. Debipur community clinic facilitated the “School Girls for Fistula Free Bangladesh program” in the villages. Conclusions: Community Clinics in Bangladesh may play a major role in prevention of early marriage, promotion of safe motherhood and prevention of female genital fistula in villages. Community clinic centered social mobilization engaging school girls would help in ending fistula in remote communities.